Crisis Communication on Social Media: Managing Reputation and Maintaining Public Trust - Larisu, Zulfiah; Zulham, Zulham (PT. Anagata Sembagi Education, 2024)
This study aims to analyze crisis communication strategies implemented by organizations in Indonesia through social media, using the Systematic Literature Review (SLR) method. This method was chosen to collect, evaluate, and analyze relevant literature, in order to obtain a comprehensive picture of crisis communication practices in Indonesia in the context of social media. The data collection process was carried out by filtering relevant scientific articles, reports, and studies related to crisis communication and social media, published through various sources such as academic journals, conferences, and industry reports. Each selected article was evaluated based on the criteria of relevance, methodological quality, and its contribution to the understanding of crisis communication in social media. The results of the study indicate that effective crisis communication in social media requires a fast, transparent, and consistent response. Organizations that successfully manage communication through social media have a greater chance of maintaining public trust and reducing the negative impact on their reputation. The speed of response is a key factor, given the very rapid spread of information on social media. In addition, transparency and consistency of messages are essential to prevent public confusion. This study concludes that organizations in Indonesia must design communication strategies that are adaptive to the dynamics of social media, by ensuring clear, accurate, open messages, and monitoring public reactions directly. Thus, effective communication can help organizations manage crises and maintain public trust.